AgTrials: Repurposing data for adaptation research - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The AgTrials database collects decades of agricultural field experiments to help understand and adapt to climate change impacts.